Empirical Research of Development Features of the Organizational Culture of Construction Enterprises - Rynkevich, N. (Економічний вісник Донбасу, 2019)
Currently, the problems of developing the organizational culture of enterprises of various types of economic activity are being updated taking into account their specifics. This allows you to achieve greater flexibility and the ability to quickly respond to changes in the internal and external environment, to strengthen competitive positions in the sales markets, which corresponds to modern business conditions. The purpose of this study is an empirical research of the organizational culture of construction enterprises, identifying trends in its development in modern conditions and improving the methodological approach to assessing the level of development. As a result of the research, the dynamics of the number of employed and hired workers in the construction industry is analyzed. The results of an expert survey are presented to identify current problems, barriers, features, trends and ways of developing the organizational culture of construction enterprises in Ukraine. An assessment of the level of development of the organizational culture of enterprises. An integrated methodology for assessing the organizational culture of construction enterprises is proposed. Testing of this methodology showed that the surveyed enterprises have an average level of organizational culture development (0.69), since the value of the integral indicator is in the range of 0.5-0.75.